An emission-tunable fluorescent organic molecule for specific cellular imaging. Issue 81 (16th August 2016) - Tang, Fu; Wang, Xiaoyu; Yao, Chuang; Chen, Shuai; Li, Lidong
Abstract : A color-tunable fluorescent molecule was synthesized and applied in specific lysosomal imaging. Abstract : A novel fluorescent organic small molecule, 4, 4′-((1 E, 1′ E )-(2-(3-aminopropoxy)pyrimidine-4, 6-diyl)bis(ethene-2, 1-diyl))bis( N, N -diethylaniline) (PPBEN ), was designed and synthesized. WhenPPBEN was dissolved in aqueous solution, its emission maximum showed a large blue shift compared with that in organic solution. The emission spectra ofPPBEN could be finely tuned by controlling the water content in organic/water mixed solutions, resulting in a sequential color change of its fluorescence as a function of water fraction. Theoretical calculations illustrated that protonation of the tertiary amine groups ofPPBEN was the main reason for this phenomenon. A pH-responsive study showed that an acidic aqueous environment increased the emission intensity ofPPBEN, further proving that protonation affected its emission properties. Cell assays showed thatPPBEN is suitable for cellular imaging. Colocalization analysis ofPPBEN with a commercial lysosome dye demonstrated its potential application in specific lysosome imaging.